1897 Tex. Gen. Laws 221- 22, ch. 155, § 1 - (:unkn) unknown (My University, 1897)
Prohibited the selling or giving to a minor a pistol, dirk, dagger, slungshot, sword cane, spear or knuckles made of any metal or hard substance, Bowie knife or any other knife manufactured or sold for the purpose of offense or defense without the consent of their parent or guardian. Punishable by fine of $25-200 and/or imprisonment for 10-30 days.
Keywords: TRANSFER - MINORS